The Review of the English Textbook: Battleplan. English for the Polish Military. Student’s Book, Level 3. Author: Jeremy Walters - Knapik, Aleksandra R. (2023)
This article provides a comprehensive review of the English textbook entitled Battleplan: English for the Polish Military. Student’s Book, Level 3. The evaluation encompasses various aspects, including content, pedagogical approach, language proficiency targets, and overall effectiveness in catering to the linguistic needs of Polish military personnel. Through a meticulous analysis, the article aims to offer insights into the strengths and potential shortcomings of the textbook, shedding light on its suitability for learners at Stanag Level 3. The review seeks to contribute to the ongoing discourse on language education within military contexts, providing educators and curriculum developers with valuable perspectives for refining language learning materials tailored to the specific requirements of the Polish military in the context of Stanag 6001examination.
Keywords: military discourse; Stanag 6001; formal writing; second language acquisition; ESL